In Vitro Hepatic Metabolism of Curcumin Diethyl Disuccinate by Liver S9 from Different Animal Species - Jithavech, Ponsiree; Ratnatilaka Na Bhuket, Pahweenvaj; Supasena, Wiwat; Qiu, Guanyinsheng; Ye, Shengqing; Wu, Jie; Wong, Tin Wui; Rojsitthisak, Pornchai (Frontiers in Pharmacology, 2020)
Liver S9 (LS9) is a nearly complete collection of all hepatic drug-metabolizing enzymes. It is a low-cost model for predicting drug metabolic activity. This study aimed to identify the suitability of using LS9 of different animal sources in drug metabolism profiling with respect to the possible translation of the in vitro outcomes to clinical studies. The in vitro hepatic metabolism of curcumin diethyl disuccinate (CDD) in LS9 of rats, dogs, monkeys, and humans was evaluated. The identity of CDD metabolites and the metabolism kinetic parameters, including degradation rate constant, in vitro/in vivo intrinsic clearance, and half-life, were determined. CDD was rapidly metabolized into monoethylsuccinyl curcumin and curcumin in LS9 of all tested species mainly by carboxylesterases (CESs), including CES1 and CES2, and butyrylcholinesterase. The in vitro intrinsic clearance of CDD was in the order of human > dog > monkey > rat, whereas that of monoethylsuccinyl curcumin in the order of dog > monkey > human > rat; this parameter was not correlated with their respective in vivo clearance, which followed the order of dog > monkey > rat > human. Therefore, in vitro drug metabolism data inferred from LS9 of nonhuman origin, especially from monkeys and dogs, cannot be used as preclinical data for human trials, as humans have a smaller liver-to-body weight ratio than monkeys, dogs, and rats. The in vivo drug metabolism is dictated by the anatomical factors of the test subject.